Dietary pattern and type 1 diabetes - Oliveira, Valzimeire do Nascimento de; Nogueira, Valéria Cristina; Machado, Soraia Pinheiro; Guedes, Maria Izabel Florindo (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2024)
Studies on nutritional epidemiology have shown associations between dietary patterns and diabetes. This study was carried out to identify dietary patterns and assess their association with the presence or absence of type 1 diabetes. In this cross-sectional study with 45 patients with type 1 diabetes and 45 healthy adult subjects, social and lifestyle demographic data were collected using structured questionnaires. Food intake was estimated using a 24-hour recall. Dietary patterns were identified by principal component factor analysis, followed by orthogonal varimax rotation. Poisson regression was used to estimate the prevalence ratios of independent variables about dependent variables. Three main patterns were identified: prudent, snack, and western. Together, they explained 34.49% of the variance. The prudent pattern was one that represents the intake of food groups recommended in a healthy diet. There was no significant association between patterns and the presence or absence of type 1 diabetes.